Liquidity at the Oslo Stock Exchange - Randi Næs; Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2008)
We analyze the relationship between the long term development in liquidity at the Oslo Stock Exchange and the Norwegian economy for the period 1980 to 2007. We calculate different liquidity measures that captures various dimensions of liquidity over time and across industry groups. Overall, we find that the liquidity at the OSE has improved over the sample period. However, the improvement is most pronounced for the largest firms on the exchange. Interestingly, some measures indicate that the implicit cost of trading has been lower in earlier periods than it is today. Another important finding is that there is a strong counter cyclical relationship between proportional transaction costs measured by the relative spread and the business cycle measured by the output gap. The average relative spread also responds very quickly to the turning points of the business cycle. This result suggest that liquidity measures provide important real time information about the current state of the economy as well as market participants expectations about future economic growth.
hdl:11250/2497776
Keywords: G12; G14; 330; liquidity; market microstructure